2019
DOI: 10.1007/s00109-019-01762-4
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of the antipsychotic drug TFP for sepsis treatment

Abstract: Sepsis is a disease responsible for the death of almost all critical patients. Once infected by virus or bacteria, patients can die due to systemic inflammation within a short period of time. Cytokine storm plays an essential role in causing organ dysfunction and septic shock. Thus, inhibition of cytokine secretion is considered very important in sepsis therapy. In this study, we found that TFP, an antipsychotic drug mainly used to treat schizophrenia by suppressing dopamine secretion, inhibited cytokine relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In TFP’s case, it had been shown to modulated immune system. It suppressed cytokine release from activated immune cells both in vitro and in vivo and improved survival rate in sepsis models (Park et al, 2019). Another study found that TFP combated respiratory and gastrointestinal bacterial pathogens probably through affecting the host immune system (Andersson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In TFP’s case, it had been shown to modulated immune system. It suppressed cytokine release from activated immune cells both in vitro and in vivo and improved survival rate in sepsis models (Park et al, 2019). Another study found that TFP combated respiratory and gastrointestinal bacterial pathogens probably through affecting the host immune system (Andersson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TFP is known to be a calmodulin inhibitor. One of other proposed modes of effects of TFP is its ability of binding to a well-known Ca 2+ binding protein, calmodulin (CaM) (Kang et al, 2017; Park et al, 2019). TFP is also shown to promote FOXO3 nuclear localization and activation to suppress breast cancer (Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparent normalization of some cytokine levels following treatment of schizophrenia with antipsychotic drugs as well as in vitro demonstrations of their ability to impact pro-and anti-inflammatory cytokines [29][30][31][32] has led to speculation and analysis that immunomodulation is a previously unrecognized component of their therapeutic effect for patients experiencing psychosis [33]. The notion of therapeutically relevant immunomodulation has been applied to lethal inflammatory conditions such as bacterial sepsis, wherein the typical antipsychotic drug trifluoperazine showed an improved survival and reduced organ damage in a preclinical model [34]. This reciprocal potential for drug repurposing is reflective of the bi-directional interactions between the immune and nervous systems, notable here for the demonstrated involvement of dopaminergic and serotonergic signaling in both processes.…”
Section: Fig 5 Immune Dysregulation and Infectious Disease Susceptibmentioning
confidence: 99%
“…Adding another level of complexity in the interaction between the dopaminergic and immune system, some studies have shown that some drugs targeting dopaminergic system might regulate inflammation. According to the critical role of dopamine in the regulation of sepsis (Torres-Rosas et al, 2014), it has recently been shown that the antipsychotic drug trifluoperazine (TFP), which suppress dopamine secretion, exerted a strong regulation of proinflammatory cytokines and increased the survival rate in animal models of sepsis (Park et al, 2019). Another example illustrating the role of antipsychotic drugs is the study of the effect of paliperidone in neuroinflammation.…”
mentioning
confidence: 99%